The income and demographic determinants of physical activity intensity: Evidence from a developing country - Cheah, Yong Kang; Azahadi, Mohd; Phang, Siew Nooi; Abd Manaf, Noor Hazilah (SAGE Publishing, 2017)
Estimating the factors affecting participation decisions of physical activity has continuously received significant research attention. However, the effects of income and demographic factors on physical activity intensity have seldom been studied thoroughly, especially in developing countries. To fill this research gap, the income and demographic determinants of the time spent on both vigorous- and moderate-intense physical activities among Malaysian adults are estimated using a censored regression model. The results are comparable to those in developed countries, such as the USA and Australia, which show that income, age, education level and being unemployed are negatively associated with the time spent on both vigorous- and moderate-intense physical activities. Compared to females, males spend more time on vigorous-intense physical activity but less time on moderateintense physical activity. The present study suggests that acquiring a better understanding of the factors that can affect physical activity intensity is important for policy development.